Short-term Clinical and Radiographic Outcomes of Transforaminal Full-endoscopic Pars Crisscross Decompression of the Exiting Nerve Root under Local Anesthesia in Adult Isthmic Spondylolisthesis - Yutaro KANDA; Fumiaki MAKIYAMA; Ryota MIO; Kozaburo MIZUTANI; Masashi KUMON; Saori SOEDA; Masatoshi MORIMOTO; Fumitake TEZUKA; Kazuta YAMASHITA; Koichi SAIRYO (Neurologia Medico-Chirurgica, 2025)
In adult isthmic spondylolysis/spondylolisthesis, a fibrocartilaginous mass, ragged edge, and decrease in disk height cause radiculopathy with intervertebral foraminal stenosis. There are few reports on the outcomes of full-endoscopic spine surgery for isthmic spondylolisthesis because of difficulty in the ragged edge resection. This study evaluated the short-term outcomes of our original full-endoscopic spine surgery technique in patients with isthmic spondylolisthesis with a focus on the “pars crisscross.” An important landmark, the pars crisscross consist of the superior articular process at S1, floating lamina, inferior articular process at L4, and pars ragged edge. The exiting nerve root can only be decompressed by complete resection of the ragged edge after confirmation of the pars crisscross. This case series includes 6 patients (mean age 63.2 ± 14.3 years) who underwent full-endoscopic spine surgery under local anesthesia for radiculopathy. The leg pain improved immediately after surgery in all patients and the mean visual analog scale score improved from 8.2 ± 1.3 preoperatively to 1.2 ± 1.1 at 2 weeks postoperatively. The neuroforaminal area at the inlet and center expanded dramatically from 184 ± 41 mm2 and 192 ± 45 mm2, respectively, before surgery to 340 ± 55 mm2 and 338 ± 80 mm2 postoperatively. No patient experienced a recurrence of leg pain, aggravation of low back pain, or spinal instability during the 3 months after surgery. full-endoscopic spine surgery pars crisscross decompression had excellent short-term clinical and radiographic outcomes. Patients who are unsuitable for general anesthesia and instrumentation surgery could be candidates for this procedure.